Knowledge as a Cultural Product: From the Sociology of Scientific Knowledge to the Cultural Studies of Science - Ali Rabbani; Zahra Maher (Taḥqīqāt-i Farhangī-i Īrān)
The main characteristic (feature) of the sociology of knowledge and science is its emphasis on the culture and cultural analysis within the scientific and technological research. This study concerns with the study of two research fields in which new sociologists of science and technology have presented their cultural analysis. These two fields include: sociology of scientific knowledge and cultural studies of science.Sociology of scientific knowledge is the first school of thought which makes the content of scientific knowledge inclined to and compliant with the cultural and sociological analysis. In SSK, the main presupposition is that “the scientific knowledge is totally arbitrary.” Accordingly, the design and evaluation of scientific theories and claims are the consequence of social interests and cultural inclinations (trends), in a way that the scientific theories become a tool for the justification, legitimating, encouragement and contentment.At the early 1990s, with the rise of crisis (chaos) within the explanations of sociology of scientific knowledge and a flood of criticism against it, the whole subjectivity of the field came to a standstill (reached an impasse) and the initiatives in scientific research were replaced by different theoretical orientations like cultural studies. In contrast to the sociology of scientific knowledge, the cultural studies of science concerns with the rejection of “explanation” and, instead, focuses on the “meaning” and “understanding”. In other words, it has come back to an old dispute between explanatory and hermeneutic approaches and those  which pursue the regulative (legalistic) comprehensiveness along the more positivistic lines.This emerging field emphasizes the issue that the uncertainty, instability, ambiguity (vagueness) and difference must be given a more important role in sciences. Cultural studies of science gave rise to a change from the sociology of scientific knowledge to a new culturalism.